Rancangan Intervensi REBT dalam Meningkatkan Kedisiplinan Santriwati di Ponpes Miftahunnajah Yogyakarta - Fitriani Rahayu (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2019)
The article describes the factors that encourage ASB students to violate and apply undisciplined while in the school and dormitory environment. So, it can be determined the type of intervention that will be used in improving ASB student discipline. This study uses a qualitative descriptive research type with a case study approach on one female student at Miftahunnajah Islamic Boarding School. Interviews and observations are used as data collection tools. The result is that violations of ASB occur because various factors such as attending a boarding school are not ASB's own desires but are forced by parents so ASB violates as a form of rejection and also peer influence. Thus, interventions suitable for use in ASB are Rational Emotive Behavior Therapy (REBT).